Desafíos organizacionales en la transformación de un modelo de negocio: el caso de impala y su impacto en la dinámica del río magdalena (2020)
The business models have organizational dynamics as a fundamental axis. When companies begin to work in unknowns territories, they try to model their experience with local talent, which sometimes, do not meet the required level for the operation. This study addresses the challenges related to organizational culture that a multina tional company must follow to operate in Colombian territory with empirical labor, in an environment of high informality. The qualitative exploratory study is based on na rratives, taken from profound interviews with both company executives and employees, revealing the strategies that allowed them to assertively generate an auspicious space for the development of a new organizational culture. It is evident how the Company, from the understanding of the situation, could successfully model a change in the culture of its employees and positively impact their involvement in terms of job stability and better living conditions, within a win/win relationship.